Finite element analysis of braced excavation in sand - Sim, Joanne (Nanyang Technological University, 2021)
The study of the effects of varying certain parameters, such as soil strength, thickness of diaphragm wall, number of struts, etc., on the retaining wall maximum lateral deflection, bending moments, and strut forces are investigated in this report, with the use of a finite element analysis software, Plaxis 2D. The analysis is based on an actual site excavation of the O6 station in Kaohsiung Rapid Transport System (KRTS). The finite element analyses indicate that the maximum lateral wall deflection increases with increasing depth of excavation and reduction in the number of strut levels. In addition, the analyses indicate that the maximum lateral wall deflection decreases with a decrease in wall embedment length, decrease in excavation width, and an increase in the friction angle of the soil. There is a positive correlation between the increase in diaphragm wall width and negative bending moment. An increase in the friction angle of the soil and decrease in wall embedment length results in a smaller negative wall bending moment while a reduction in number of struts causes the retaining wall to have a higher negative bending moment.